Performance Zoning - Byrd Cranston; Connor Susan; Heyman Judy; Kendig Lane (Planners Press, 1980)
Acknowledgements, The Concept of Performance Zoning, Introduction, Variables, Design, The Standards, Site Capacity and Land Use Intensity, Bufferyards, Housing, Transportation, Putting It All Together, Model Ordinance, Theory and Technical Aspects, Notes, Appendix.